Therapeutical Approach to Arterial Hypertension - Current State of the Art - Radosavljevic, Milica; Vučević, Danijela; Samardžić, Janko; Radenkovic, Miroslav; Radosavljević, Tatjana (Current Medicinal Chemistry, 2024)
Arterial hypertension (AH) is recognized as the most common illness within the group of cardiovascular diseases and the most massive chronic non-infectious disease in the world. The number of hypertensive patients worldwide has reached 1.28 billion, contributing to an increase in cardiovascular diseases and premature death globally. The high prevalence of hypertension emphasizes the importance of effectively treating this condition. Elevated blood pressure often leads to lethal complications (heart failure, stroke, renal disorders, etc.) if left untreated. Considering an increase in AH prevalence in the future, a successful therapeutical approach to this disease and its complications is essential. The goal of AH treatment is to maintain normotensive blood pressure through various approaches, including lifestyle changes, a well-balanced diet, increased physical activity, psychoeducation, and, when necessary, pharmacotherapy. The evolving pharmacotherapeutic landscape reflects the progress made in our understanding of hypertension and emphasizes the need for continuous innovation to meet the challenges posed by this prevalent global health concern. The journey toward more effective and tailored treatments for hypertension is ongoing, and the introduction of new medications plays a pivotal role in shaping the future of antihypertensive pharmacotherapy.
Keywords: hypertensive crisis